Ο Ανδρέας Μουστοξύδης, ο Βαρθολομαίος Κουτλουμουσιανός και το Υπόμνημα Ιστορικόν περί της νήσου Ίμβρου: - ΖΑΝΟΥ ΚΩΝΣΤΑΝΤΙΝΑ (Μνήμων, 2012)
Konstantina Zanou, Andrea Mustoxidi, Bartolommeo Cutlumusiano and the Υπόμνημα Ιστορικόν περί της νήσου Ίμβρου The starting-point of the article is the recent reprint of Andrea Mustoxidi’s and Bartolommeo Cutlumusiano’s book Υπόμνημα Ιστορικόν περί της νήσου Ίμβρου (Historical memorandum on the Island of Imbros, Constantinople 1845) by the Association for the Protection, Solidarity and Viable Development of Imbros (Istanbul 2010). The article offers an account of the history and significance of this neglected book. In addition, building on an older treatise of K. Th.Dimaras and enriching it with new archival material, it revisits the Mustoxidi-Cutlumusiano relationship and discusses these two intellectuals’ involvement in the reformatory practices of Kapodistrias’ government in matters of religion and education.